ARTIKEL STUDI KELAYAKAN BISNIS “Analisis Studi Kelayakan Bisnis Mafia Sushi” - Mohammad Afrizal Miradji; Achmad Riyan Efendi; Afidah Sal Sabila; Asyifa Berlianasari Tamara; Hana Amiratul Laili; Muhammad Farhan Adiyatma Putra; Yohanes Yanto Lung; Yustisia Hima Nayola (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Current business opportunities are very helpful to the community's economy, one of which is the food business, because all people need food to meet their food needs. At present there are many beginners who are trying to innovate food to be different and hopefully attract consumers. Mafia Sushi is one of our innovations in the food sector so that consumers are interested in buying our products. Currently, the most commonly encountered sushi is ordinary sushi wrapped in nori, but our product is different. Our product is Fried Sushi which we coat with panir flour with our own sauce. Our products have affordable prices that can be enjoyed by all groups of people